Islamic education and the challenges of community life in the era of society 5.0 - Anisah Azzahra; M. Sirozi (Universitas Papua, 2025)
The progress of human civilization has now entered the era of society 5.0. In this era, technology plays a vital role in simplifying community activities. However, this era poses challenges, such as increasing individual competence and potential so that technology does not replace them. In addition, the value of tolerance and social interaction is decreasing due to dependence on technology. Islamic education can be a solution to face these challenges because of its universal nature. This research aims to explain how Islamic education can answer issues that arise in people's lives in the era of Society 5.0. The method is literature; the data source is from books, articles, websites, and the Quran, which are then analyzed to conclude. The results of the study show that Islamic education can integrate the use of technology with Islamic values. This aims to promote the wise use of technology without eliminating the essence of positive character and social values as the foundation. Thus, Islamic education can be the central pillar of forming a better society in the era of society 5.0.